The Gobi Khulan: A Flagship Species for Mobility - Kaczensky, Petra; Ganbaatar, Oyunsaikhan; Dejid, Nandintsetseg; Buuveibaatar, Bayarbaatar (Acta Mongolica, 2023)
Khulan, the Asiatic wild ass, have been eradicated from most of their former range. The Mongolian Gobi currently holds more than 80% of the global population and constitutes more than 70% of the global breeding range and therefore is the most important stronghold of the species. In the Mongolian Gobi, individual khulan roam over thousands of square kilometers annually and their movements are among the largest reported for terrestrial mammals globally. The high mobility of khulan plays a critical role for the ecosystem functioning of the Mongolian Gobi, including large-scale seed dispersal and provision of water holes for other wildlife. Khulan also have non-consumptive aesthetic and naturalistic values for local residents and harbor the potential for wildlife tourism and subsistence hunting. The species is currently listed as Near Threatened in the International Union for Conservation of Nature Red List, but remains under close scrutiny because multiple developments which negatively impact the size, quality and functional connectivity of the Gobi–Eastern Steppe ecosystem are happening simultaneously and at an unprecedented speed in an ecosystem which so far has remained at a near natural stage. These developments are the: 1) dramatic increase in livestock numbers and a change in the traditional herding practice, 2) rapid development of the resource extraction sector, and 3) expansion and upgrading of the transport infrastructure to meet the needs of the mining sector and allow Mongolia to connect to international markets. The paper explores how these threats may affect khulan in the future and why khulan are an ideal flagship species for mobility and landscape connectivity.